The Influence of Book Tax Differences, Operating Cash Flow, Leverage, and Firm Size towards Earnings Persistence - Maqfiroh, Catur Sari; Kusmuriyanto, Kusmuriyanto (Universitas Negeri Semarang, 2018)
The purpose of this research is to obtain empirical evidence concerning the influence of book tax differences, operating cash flow, leverage, and firm size to earnings persistence. Population in this research is company of consumer goods industry sector which registered in Indonesia Stock Exchange in 2011-2016. Years observed are 2012-2015. Sampling technique is using purposive sampling, gained 22 samples out of 33 companies. There are 85 units of analysis in this study. The analysis techniques used are descriptive statistic and multiple regression by using SPSS program. The result of the research shows that book tax differences indicated by large negative book tax differences has significant and negative influence on earnings persistence. Besides, large positive book tax difference has no influence on earnings persistence. Operating cash flow and firm size in this study are proved to have no influence on earnings persistence. Leverage is proved to have negative and significant influence on the persistence of earnings. The conclusion of this research is that earnings persistence is influenced by large negative book tax difference and leverage.